New Trend in Toxicological Screening Using Volumetric Absorptive Microsampling (VAMS) and High-Resolution Mass Spectrometry (HR/MS) Combination - Pascal Houzé; Ilona Borowski; Eugénie Bito; Romain Magny; Athina Morcos; Sebastian Voicu; Bruno Mégarbane; Laurence Labat (Molecules, 2023)
In toxicology, screenings are routinely performed using chromatographic methods coupled to detection systems such as high-resolution mass spectrometry (HR/MS). The increase in specificity and sensitivity of HRMS is responsible for the development of methods for alternative samples such as Volumetric Adsorptive Micro-Sampling. Whole blood overloaded with 90 drugs was sampled with 20 µL MitraTM to optimize the pre-analytical step as well as to determine the identification limits of drugs. Elution of chemicals was carried out in a solvent mixture through agitation and sonication. After dissolution, 10 μL was injected into the chromatographic system coupled to the OrbitrapTM HR/MS. Compounds were confirmed against the laboratory library. The clinical feasibility was assessed in fifteen poisoned patients using the simultaneous sampling of plasma, whole blood and MitraTM. The optimized extraction procedure allowed us to confirm 87 compounds out of the 90 present in the spiked whole blood. Cannabis derivatives were not detected. For 82.2% of the investigated drugs, the identification limits were below 12.5 ng·mL−1, with the extraction yields ranging from 80.6 to 108.7%. Regarding the patients’ analysis, 98% of the compounds in plasma were detected in MitraTM compared to whole blood, with a satisfying concordance (R2 = 0.827). Our novel screening approach opens new insights into different toxicologic fields appropriate for pediatrics, forensics or to perform mass screening.